MODERN PRINCIPLES OF HIGHER EDUCATION SYSTEM MODERNIZATION AND THE PROCESSES OF INTERNATIONAL INTEGRATION: THE CASE OF UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the modernization processes of the higher education system in Uzbekistan, highlighting contemporary principles and the country’s integration into the global education space. It presents the main directions of modernization and reveals the structural, legal, and pedagogical transformations carried out in the republic. The paper analyzes the international integration of Uzbekistan’s higher education system based on sociological surveys conducted among professors, researchers, and students. It identifies existing challenges and potential solutions, while also outlining future priorities. The article concludes that accelerating integration into the global educational space requires active cooperation with international educational institutions, strengthening legal frameworks, and developing the scientific potential of the country.